A hierarchical fabrication method and crushing response of metallic 3D re-entrant honeycomb. (July 2022) - Pei, Lian-Zheng; Qi, Chang; Yang, Shu; Ma, Yuan-Hang; Wu, Peng-Cheng
Abstract: Due to the negative Poisson's ratio (NPR) effect, auxetic structures such as re-entrant honeycombs show excellent energy absorption and force mitigation capabilities under crushing load. Compared with two-dimensional (2D) auxetic structure, three-dimensional (3D) ones are expected to have better performance, but they are more difficult to fabricate. In this study, a hierarchical fabrication method for metallic 3D re-entrant honeycomb (3D-RH) using traditional manufacturing techniques is proposed. A 3D-RH specimen was crafted and tested under quasi-static crushing condition. The finite element (FE) model was established and verified by the experimental results. The numerical simulation results showed that the friction condition between 3D-RH specimen and loading surfaces has a great influence on the deformation mode of specimen. Moreover, the energy absorption capability of 3D-RH was numerically compared with a similar structure, i.e., the warp and woof periodic auxetic cellular (WWPAC) structure. The results showed that the specific energy absorption ( SEA ) of 3D-RH is 1.59 times that of WWPAC and the 3D-RH outperformed the latter in lightweight performance. Finally, the blast resistance of 3D-RH sandwich panel was numerically studied. Compared with 2D re-entrant expanded honeycomb (2D-REH) core, 3D-RH core can reduce the maximum deflection of lower face-sheet by 14.6%, and increase SEA by 20.5%, showing better blast resistance. Highlights: A hierarchical fabrication method of metallic 3D-RH has been proposed. The method uses traditional manufacturing techniques to reduce fabrication cost. The friction coefficient can alter the deformation mode of 3D-RH under crushing. The energy absorption per unit mass of 3D-RH is greater than that of the WWPAC. The 3D-RH shows better anti-blast performance than the 2D-REH.